HU and IHF, two homologous histone-like proteins of Escherichia coli, form different protein-DNA complexes with short DNA fragments. - Bonnefoy, E (1991)
Using the gel retardation technique we have studied the protein-DNA complexes formed between HU--the major histone-like protein of Escherichia coli--and short DNA fragments. We show that several HU heterodimers bind DNA in a regularly spaced fashion with each heterodimer occupying about 9 base pairs. The alpha 2 and beta 2 HU homodimers form the same structure as the alpha beta heterodimer on double stranded DNA. However when compared to the heterodimer, they bind single stranded DNA with higher affinity. We also show that HU and the Integration Host Factor of E. coli (IHF) form different structures with the same DNA fragments. Moreover, HU seems to enhance the DNA-binding capacity of IHF to a DNA fragment which does not contain its consensus sequence.